A PKB-SPEG signaling nexus links insulin resistance with diabetic cardiomyopathy by regulating calcium homeostasis - Chao Quan (Nature Portfolio, 2020)
Molecular mechanisms linking myocardial insulin resistance to diabetic cardiomyopathy are incompletely understood. Here the authors show that myocardial insulin resistance impairs a PKB-SPEG-SERCA2a signaling axis, which contributes to the development of diabetic cardiomyopathy.